Contributions of Interleukin-1 Receptor Signaling in Traumatic Brain Injury - Thome, Jason G.; Reeder, Evan L.; Collins, Sean M.; Gopalan, Poornima; Robson, Matthew J. (Frontiers in Behavioral Neuroscience, 2020)
Traumatic Brain Injury (TBI) in various forms affects millions in the United States annually. There are currently no FDA approved therapies for acute injury or the chronic comorbidities associated with TBI. Acute phases of TBI are characterized by profound neuroinflammation, a process that stimulates the generation and release of proinflammatory cytokines including interleukin-1α (IL-1α) and interleukin-1β (IL-1β). Both forms of IL-1 initiate signaling by binding with interleukin-1 receptor type 1 (IL-1R1), a receptor with a natural, endogenous antagonist dubbed interleukin-1 receptor antagonist (IL-1Ra). The recombinant form of IL-1Ra has gained FDA approval for inflammatory conditions such as rheumatoid arthritis, prompting interest in repurposing these pharmacotherapies for other inflammatory diseases/injury states including TBI. This review summarizes the currently available preclinical and clinical literature regarding the therapeutic potential of inhibiting IL-1-mediated signaling in the context of TBI. Additionally, we propose specific research areas that would provide a greater understanding of the role of IL-1 signaling in TBI and how these data may be beneficial for the development of IL-1 targeted therapies, ushering in the first FDA-approved pharmacotherapy for acute TBI.